Kelayakan Finansial Usaha Pengolahan Daging Rajungan di Kabupaten Bombana (Studi Kasus: Mini Plant Bombana Jaya) - Mira Wati; Budiyanto Budiyanto; Ine Fausayana (Jurnal Sosio Agribisnis, 2020)
This study aims to analyze the financial feasibility of the crab meat processing business at the Bombana Jaya Mini Plant in Bombana Regency, Southeast Sulawesi Province. The method used is a case study by collecting data and information from business owners, previous research results and related agencies. To determine the financial feasibility of crab meat processing business used analysis of Net Present Value (NPV), Net Benefit Cost Ratio (NBCR), Internal Rate of Return (IRR), Payback Period and sensitivity. The results of the study show that financially, the crab meat processing business at the Bombana Jaya Mini Plant is feasible to develop.Key words: crab; mini plant; feasibility